Association between weight change and the predicted 10-year risk for atherosclerosis cardiovascular disease among U.S. older adults: data from National Health and Nutrition Examination Survey 1999-2018 - Yuxuan Peng; Yuxuan Peng; Yuxuan Peng; Hongzheng Li; Hongzheng Li; Hongzheng Li; Feifei Liao; Feifei Liao; Feifei Liao; Jieming Lu; Jieming Lu; Jieming Lu; et al. (Frontiers Media S.A., 2023)
BackgroundIt remains controversial regarding the association between weight change and cardiovascular disease risk in older adults (aged ≥60 years). This study aimed to evaluate the association between weight change and the predicted 10-year atherosclerotic cardiovascular disease (ASCVD) risks in older adults.MethodsThis study used data from the National Health and Nutrition Examination Survey (NHANES). Older adults aged 60-79 years who were free of self-reported ASCVD at the time of the NHANES interview were included. Data were collected from January 1999 to December 2018 and analyzed in March 2022. We focused on the associations between weight change and the 10-year ASCVD risks with the percentage change in weight during short-term (1 year) and long-term (10 years), which categorized as moderate to high weight loss (≥10%), small weight loss (5.1-9.9%), stable weight (±5%), small weight gain (5.1-9.9%), and moderate to high weight gain (≥10%).ResultsThe number of participants was 1,867 (mean age 67.49 years; 42.10% female) for the long-term interval (10 years) in our analysis, and 1894 for the short-term interval (1 years). We only observed an inverse association between long-term weight loss and the 10-year ASCVD risk in fully adjusted model (loss ≥ 10%: β = 2.52, 95%CI = 0.98, 4.05; loss 5.1% ~ 9.9%: β = 2.99, 95% CI = 1.30, 4.68), but all intervals of weight gain ≥5% were not significant associated with higher risk than stable weight. However, in the subgroup analyses, the association between long-term weight loss and the 10-year ASCVD risk was not significant in old-old (aged 75-79), obesity (BMI ≥ 35 kg/m2), intentional weight loss, moderate physical activity and diabetics.ConclusionOlder adults (aged 60-79 years) with weight loss >5% over the past 10 years have excess predicted 10-year ASCVD risk. Our study supports the benefits of stable weight in promoting cardiovascular health in older adults.